2013
DOI: 10.1136/jnnp-2013-305321
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of functional (psychogenic) motor symptoms: a systematic review

Abstract: Existing follow-up studies of functional motor symptoms give us some insights regarding outcome and prognostic factors but are limited by their largely retrospective and selective nature. Overall, prognosis appears unfavourable. The severity and chronicity of functional motor symptoms argues for larger prospective studies including multiple prognostic factors at baseline in order to better understand their natural history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
231
3
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(253 citation statements)
references
References 40 publications
(122 reference statements)
10
231
3
9
Order By: Relevance
“…However, patients with FMD are generally reported to have poor outcome, with persistent symptoms reported in 65-95 % patients [2][3][4]. Such reports, most of which are based in tertiary referral centers may overstate poor outcome, but a recent systematic review of outcome in patients with functional motor symptoms, in general, also found outcome, in general, to be poor, with most studies finding at least 50 % of patients to still be symptomatic at long-term follow-up [5].…”
Section: Introductionmentioning
confidence: 97%
“…However, patients with FMD are generally reported to have poor outcome, with persistent symptoms reported in 65-95 % patients [2][3][4]. Such reports, most of which are based in tertiary referral centers may overstate poor outcome, but a recent systematic review of outcome in patients with functional motor symptoms, in general, also found outcome, in general, to be poor, with most studies finding at least 50 % of patients to still be symptomatic at long-term follow-up [5].…”
Section: Introductionmentioning
confidence: 97%
“…3 Given the frequency, consequences, prognosis, and burden, FND has been called a "crisis for neurology." 4 Despite this, FND is poorly understood.…”
mentioning
confidence: 99%
“…Compared with patients suffering from disease pathology, patients with functional disorders suffer from more distress and disability, more social isolation and are more likely to be receiving disability-related state financial benefits [3,4]. Although functional disorders can remit spontaneously, the prognosis is often poor [5][6][7].…”
Section: Introductionmentioning
confidence: 99%